Architecture for clinical decision support system (CDSS) using high risk pregnancy ontology - Lam, Jostinah; Abdullah, Mohd Syazwan; Supriyanto, Eko (Asian Research Publishing Network (ARPN), 2015)
Shortage of medical professionals in the rural area has been one of the reasons why maternal mortality is still very high.Midwife family program had been introduced to overcome the shortage but the lack of skills in recognizing high risk pregnancy becomes another factor of high maternal mortality rate.A good prenatal care program will help to identify the danger in time and provide early management.Therefore, this paper provides solution by introducing a new architecture of clinical decision support system (CDSS) in the domain of high risk pregnancy. The proposed architecture is composed of seven main components.The ontological approach was used to develop the knowledge repository in the CDSS architecture.The need for CDSS was investigated through interview session, questionnaire distribution and observation.In addition, the comparison with other CDSSs approach is also highlighted in the paper.